PENGGUNAAN MATERIAL KAYU PINUS DAN KOMPOSIT SERAT RAMI PADA BILAH TURBIN ANGIN TERHADAP DAYA YANG DIHASILKAN - Wardhana, Abdul Ghofur Syamdatu; Abizar, Haris; Ramdani, Sulaeman Deni (Universitas Sarjanawiyata Tamansiswa, 2024)
The objectives of this research are (1) To find out the effect of hemp fiber composite material on wind turbine blades on the power produced., (2) To know the effect of pine wood material on wind turbine blades on the power produced, (3) To know the comparison of wind turbine blades using hemp fiber and pine wood composite materials on electrical power output. This research was carried out using an experimental method using samples of pine wood and hemp fiber composite materials. Data collection was carried out for 2 days with 5 minute intervals in the morning, afternoon and evening with direct observation and documentation. Data analysis was carried out using a quantitative approach. The research results stated that (1) testing pine wood blades obtained the highest data of 135.24 Watts on the first day during the day and the lowest, namely 8.89 Watts on the first day in the afternoon. (2) The highest data obtained by the hemp fiber composite blade was 119.21 Watts on the first day of testing in the afternoon and the lowest was 4.77 Watts on the second day of testing in the afternoon. (3) There is a difference between the power produced by pine wood material and hemp fiber composite material. So, the final result of obtaining electrical power from pine wood material blades is higher than that of hemp fiber composite material.